The Effectiveness of Group Guidance with Desa Bahagia Game to Improve Students’ Prosocial Behaviors - Putra, Azis Andika; Wibowo, Mungin Eddy; Sugiharto, Dwi Yuwono Puji (Jurnal Bimbingan Konseling, 2019)
This study aimed to improve students’ prosocial behaviors through Desa Bahagia (happy village) game activities. The study used experimental method with the design of one group pre-test – post-test, and employed purposive sampling technique to choose 10 students of the Eleveth Grade or Class XI in Senior High School as the research subjects. Further, based on data analysis, it was known that group counselling with Desa Bahagia game was proved effective to improve students’ prosocial behaviors, showing (z = -2.805, p < 0.01). These findings assert that group guidance with Desa Bahagia game can be an effective alternative to maximize the quality of group guidance service.